Development of Micro-Enterprises in Rural Areas in the Warmińsko-Mazurskie Voivodship - Brodziński, Zbigniew; Bojkowska, Emilia; Janek, Sebastian (Olsztyn Economic Journal, 2020)
This study identified changes in the number and growth rates of micro-enterprises in the rural areas of individual districts in the Warmińsko-Mazurskie Voivodship in the years 2010-2017. An analysis of secondary GUS data was conducted as part of the study. The Warmińsko-Mazurskie Voivodship data was compared to the nation-wide data. The micro-entrepreneurship index and absolute increases were used in the study, which revealed an increase in the number of micro-enterprises over the period under analysis in all districts of the Warmińsko-Mazurskie Voivodship. However, the non-agricultural micro-entrepreneurship index in the region was lower in all of the years under study than the average in Poland. No increased concentration of micro-enterprises was found in the districts neighbouring the largest cities in the voivodship, except in the district of Olsztyn, where the largest absolute increase in the micro-entrepreneurship index was noted in the successive years covered by the analysis.